Diffusion of cytotoxic concentrations of nitric oxide generated luminally at the gastro-oesophageal junction of rats. Issue 8 (28th April 2005) - Asanuma, K; Iijima, K; Sugata, H; Ohara, S; Shimosegawa, T; Yoshimura, T
Abstract : Background: In humans, high concentrations of nitric oxide are generated luminally at the gastro-oesophageal junction through enterosalivary recirculation of dietary nitrate. Aim: To investigate whether luminal nitric oxide can diffuse into the adjacent digestive tissue and alter tissue integrity. Methods: We designed an animal model using Wistar rats in which physiological concentrations of nitrite and acidified ascorbic acid were administered separately so that the two reactants first meet to form nitric oxide at the gastro-oesophageal junction. Luminal and tissue concentrations of nitric oxide were measured with an electrode and an electron paramagnetic resonance spectrometer, respectively. Concentrations of glutathione in the tissue were measured as a marker of nitrosative stress. Results: High concentrations of luminal nitric oxide were generated locally at the gastro-oesophageal junction of nitrite administered rats, reproducing a phenomenon observed in humans. High levels of nitric oxide were also detected largely in the superficial epithelium of the gastro-oesophageal junction. The concentration of tissue glutathione at the gastro-oesophageal junction was significantly lower in nitrite administered rats compared with control rats, whereas that in the distal stomach was similar in the two rat groups. Conclusions: Using an animal model, this study demonstrated that nitric oxide generated in the lumen diffuses into the adjacent gastric tissue to a substantial degree, leading to localised consumption of glutathione in the tissue. Nitrosative stress induced by this mechanism may be involved in the high prevalence of inflammation and metaplasia, and subsequent development of neoplastic disease at this site.